THE GOOD GOVERNANCE IMPLEMENTATION AT VILLAGE LEVEL IN EAST NUSA TENGGARA PROVINCE - Ela Lesmanawaty Wargadinata; Ika Sartika (Universitas Padjadjaran, 2019)
The Government of Indonesia has implemented a progressive policy on rural development since 2015 through distributing enormous budget that has never been given so far, called as village fund policy. This policy is intended to empowering of poor people in the village throughtout the development of village infrastructure to eliminate poverty or for poverty alleviation. In the period of 2015-2018, the budget increased significantly, reach one billion IDR for each village accros the country. From the national spending recorded that in 2015, the village fund reaches IDR 20.7 trillion, increased to 47 trillion in 2016, 60 trillion in 2017 and 60 trillion in 2018. These funds utilized mostly for basic rural infrastructures such as road, bridges, drainage, irrigation or clean water supply. Based on the field evidence show that the policy does not yet touch the basic need of the poor people in a rural area. The rural poor people considered that the program was still not given benefits for them, especially in the economic area. This paper explores the implementation of village fund policy in East Nusa Tenggara (NTT) as the third poorest province in Indonesia through good governance lenses. Based on quantitative analyses, the result shows that participation and responsiveness reveal as determinant factors to the success of village fund policies.